2014
DOI: 10.1080/15222055.2014.886648
|View full text |Cite
|
Sign up to set email alerts
|

Size and ATP Content of Unfertilized Eggs from Farmed and Wild Atlantic Salmon in Newfoundland

Abstract: In Newfoundland and Labrador (hereafter, Newfoundland), all farmed Atlantic Salmon Salmo salar originate from the Saint John River, New Brunswick, strain, raising the question of potential impacts of escapees on wild, genetically distinct stocks. Unfertilized eggs of farmed and wild salmon were assessed for diameter, mass, adenosine triphosphate (ATP) content, and fertilization success, this is the first study to assess ATP content in Atlantic Salmon eggs. Results demonstrated that farmed salmon egg mass (0.10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
23
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(27 citation statements)
references
References 28 publications
3
23
1
Order By: Relevance
“…() found no differences in fertilization attributable to a difference in gamete traits, while the trend observed in this study and the results of Lush et al . () highlight an egg quality effect despite a very high sperm to egg ratio. Despite the dissimilarity in fertilization rates, the present data confirm Yeates et al .…”
Section: Sperm Cell Densities Atp Levels Enzymatic Activities Flagmentioning
confidence: 95%
See 4 more Smart Citations
“…() found no differences in fertilization attributable to a difference in gamete traits, while the trend observed in this study and the results of Lush et al . () highlight an egg quality effect despite a very high sperm to egg ratio. Despite the dissimilarity in fertilization rates, the present data confirm Yeates et al .…”
Section: Sperm Cell Densities Atp Levels Enzymatic Activities Flagmentioning
confidence: 95%
“…Lush et al . () showed that the variability of egg mass among females was equivalent in both Saint John strain farmed and Little River wild females. In addition, variation in ATP egg −1 revealed differences between wild and farmed S .…”
Section: Sperm Cell Densities Atp Levels Enzymatic Activities Flagmentioning
confidence: 96%
See 3 more Smart Citations